CONTUINITY OF CARE (COC) MIDWIFERY CARE IN NY.M WITH BLOCKED DUCTS AT PMB AZRI YANI DELI TUA DISTRICT, DELI SERDANG REGENCY IN 2024 - Br Sihombing, Meliana; Dr. ROSMANI SINAGA, S.E, M.M; Eva Ratna Dewi,SST,MKM; Dr. Herna Rinayanti Manurung,S.Tr.Keb,Bd.M.Kes; Anita Sinaga; Angelina Simbolon, (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
The depiction of welfare in society is an indicator in carrying out interventions in the development of maternal and child health in a country where the number of maternal mortality rates (IMR) and infant mortality rates (IMR) are a goal and Sustainable Development Goals (SDGs) with the target of reducing maternal and child mortality rates in 2030 by achieving the number of live births and children/infants (IMR) who achieve a healthy life (SDGS-2017). The results obtained from the Preliminary Survey at the Niar Clinic in Medan Amplas District in 2022. The author earlier asked for permission to conduct a study at PMB Azri Yani, a writing to get the number of pregnant women in making ANC visits totaling 50 people, INC as many as 12 people, Postpartum as many as 12 people, BBL as many as 12 and KB as many as 8 people, and among the 50 pregnant women, 1 pregnant woman who had experienced anemia in pregnancy and a mother who felt dizzy, blurred vision, during this pregnancy, the mother said that it was her first time visiting a health facility because the home address and health facilities were very far away and no one took her to make a visit and did not fulfill the recommendations in fulfilling the ANC examination. The application in 2022 entitled the factors causing pregnant women who make or influence in making repeat visits (ANC) in the Medan Deli Tua Health Center area.